Correlation between Serum Uric Acid Level and Severity of Coronary Artery Stenosis in Patients with Acute Coronary Syndrome - Diding Heri Prasetyo; Sally Aman Nasution; Idrus Alwi; Murdani Abdullah (Majalah Kedokteran Bandung, 2021)
Acute coronary syndrome (ACS) is a life-threatening disease which remains one of the causes of high morbidity and mortality despite the current advances in treatment. The relationship between the serum uric acid  (SUA) level and ischemic heart disease continues to be controversial and still has not been established as a cardiovascular risk factor. The cooperative interaction between the two factors has not yet fully understood. Prior epidemiological evidence of the causal relationship between the too is still argumentative. Various studies have been done using the same methods; yet, the outcomes were different. This study aimeds to conduct a meta-analysis to synthesize the results of recent studies in order to obtain accurate quantitative data. This systematic study followed the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guideline and studies published in the period of  January 2010 to May 2020 were screened using the Cochrane Library, Ebsco, Medline/PubMed, ProQuest and Science Direct as the sources. Meta-analysis was conducted to synthesize the association between the SUA level and severity of coronary artery stenosis using random effect model to account for possible study heterogeneity. Heterogeneity was assessed using I2 and the meta-analysis was performed using Comprehensive Meta Analysis Version 3 (CMA3) software. Five studies (n = 601 subjects) identified a correlation between serum uric acid level and Gensini score (r = 0.548; p <0.001) in ACS patients. Heterogeneity bias was found in the analysis, whereas publication bias was not found. Thus, the severity of coronary artery stenosis in patients with ACS is positively correlated with serum uric acid level.